Gender-Inclusive Governance in BMT: The Role of Women in Leadership and Decision-Making - Asytuti, Rinda; Afna, Inda Millata; Kamalia, Aini Anjali Putri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The role of women in Islamic microfinance institutions, particularly Baitul Maal wat Tamwil (BMT), is a crucial aspect of modern Islamic economic development. Although Islamic principles emphasize justice and equality, women’s representation in BMT leadership and decision-making remains limited, even though they are primary beneficiaries and possess strong social awareness of members’ needs. This study aims to analyze the role and influence of women in BMT governance while identifying gender gaps in the adoption of Islamic finance. It also examines the factors that shape Islamic finance adoption among small and medium enterprises and explores gender-based differences. Using qualitative methods through in-depth interviews and focus group discussions with BMT management and female members, combined with quantitative analysis using a simple logistic model, this research assesses key determinants of women’s decision-making. Fairlie’s decomposition analysis is applied to evaluate gender disparities in the implementation of Islamic financial systems with a sample of 1,358 SMEs. The findings show that women’s involvement in BMT leadership enhances transparency, social empathy, and alignment with maqāṣid al-sharī‘ah. Moreover, gender differences in Islamic finance adoption highlight the need for more inclusive governance strategies to ensure justice and equal participation. The study emphasizes the importance of policies that strengthen women’s roles and contribute to more inclusive, equitable, and sustainable BMT development.